(untitled) (The Review of Diabetic Studies, 2025)
Objective: To evaluate the influence of occupational and non-occupational exposure to mercury, occupational health and safety conditions on the clinical effects experienced by a group of artisanal and ancestral miners in Colombia. Materials and methods: a cross-sectional quantitative study, primary sources of information, and an assisted survey of 103 gold miners. Exploratory, bivariate and multivariate analysis, Bayesian networks to probabilistically model three risk scenarios; current conditions, maximum and minimum possible degree of exposure. Results: Most miners do not report obvious clinical symptoms, prolonged exposure and without adequate protection increases the risk of developing neurological and respiratory effects. The scenario of greater exposure, the incidence of tremors, paresthesia and respiratory problems increased dramatically. Conclusion: The clinical effects evaluated showed a behavior, in which the risk is due to a deterministic influence and responds to individual and collective conditions, they can be linked to the social, economic, political, territorial, and public order levels, hence the exposure variables only explain a relative percentage of this public health problem. There is a need for a comprehensive approach that encompasses occupational and non-occupational protection, with a view to reducing the use and routes of exposure to mercury.